COMPARATIVE CHARACTERISTICS OF THE DEVELOPMENT OF INFLUENZA INFECTION IN MACROPHAGES DIFFERENTIATED FROM MONOCYTES OF THP-1 (INFLUENZA A VIRUSES OF SUBTYPES H1, H5 AND H9) - T. M. Sokolova (Sankt-Peterburg : NIIÈM imeni Pastera, 2018)
Macrophages (Mf) play an important role in the pathogenesis of influenza infection, but the obtaining of Mf in large quantities is difficult. In connection with this, in the present study, THP-1 monocytes differentiated by phorbol ether (PMA) into macrophages (MF) were used to study influenza infection. Differentiated cells — THP-PMA Mf were infected with pandemic А(H1N1)pdm09 and avian influenza A viruses H5N2 and H9N2. Differences in the levels of penetration of viral RNA (gene M1) and nucleocapsid (NP) proteins of the investigated viruses were found. The levels of expression of viral RNA and proteins were significantly higher in cells infected with avian viruses compared to pandemic viruses. Of particular interest is the phenomenon of prolonged intracellular presence of viral RNAs and nuclear localization of NP protein. However, no infectious or haemagglutinating activity of the virus of all subtypes studied in the culture liquid was detected up to 96 h. This indicates the abortive nature of influenza infection in THP-PMA Mf. Thus, MF performs a special function of depositing viral components and delivering them to the sites of inflammation. The blocking mechanism in human and avian influenza A viruses with different pathogenicity may differ, due to the existence of multiple mechanisms of escape from the immune response. As a result of infection with the human virus А(H1N1)pdm09, the infection developed slowly and caused death of 25% of the cells by 72 h, whereas in the case of infection with avian viruses, 50% of the cells died after 24 hours and by 72 h all the THP-PMA MF died. Preprocessing with recombinant IFNα2b had a protective effect, suppressing the accumulation of the NP protein of the A/H5N2 virus in the THP-PMA Mf nuclei. The obtained data allow us to conclude that one of the reasons for the different course and outcome of influenza infection in human infection with influenza A viruses is the sensitivity of human macrophages to avian influenza viruses of subtypes H5 and H9 as compared to the pandemic virus. Our result on the THP-PMA Mf model is consistent with reports on the blocking of the stages of the release of infectious influenza A virions in primary cultures of monocytic and alveolar MF. Massive death of MF caused by avian influenza viruses explains their high pathogenicity.